Quality and Accuracy of Recording in Necessary Immunization Report Through Data Quality Assessment in Blitar - Meida Sucsesa; Arief Hargono (Universitas Airlangga, 2018)
Background: The achievement of Universal Child Immunization (UCI) for villages in the national level or regional level was expected to reach at least 90%. In East Java, the prevalence of diphtheria was found spread in all district or city regions and highest cases were found in Blitar district with 57 cases in 2017. Purpose: This study was aimed to analyze the problems in immunization from quality and data accurate, especially recording and reporting the complete necessary immunization. Methods: The study was conducted descriptively through cross sectional design. Respondents were from 18 immunization officer of UCI village status and 6 immunization officer of non-UCI village status in public health center in Blitar district. The independent variables were the accuracy of babies’ cohort data reported by the public health center, recording, and reporting immunization result. Results: Based on recording of immunization data in some qualified public health center was good. However, the weakness of this system was in the reporting system as the immunization results were reported after the deadline given by the public health center. There were differences on reporting the babies’ cohort with public health center reports. Conclusion: The reporting system of complete basic immunization record in public health center was classified as properly managed so that it can be used in improving immunization program quality, but, in some public health centers were still underrated.